Marketinška koncepcija kao preduvjet održivosti novih poduzetničkih pothvata u Bosni i Hercegovini / Marketing Conception as a Prerequisite for the Sustainability of New Entrepreneurial Ventures in Bosnia and Herzegovina - Bekić, Ivana; Saračević, Nerma; Ivanković, Jadranka (Pregled: časopis za društvena pitanja / Periodical for social issues, 2024)
Sustainable competitiveness is essential for the initial survival and long-term success of a company. Looking at competitiveness through the lens of sustainability, business success is not measured solely by profitability and market share, but by consumer satisfaction and loyalty. Meeting consumer expectations effectively attracts attention, creates long-term demand, and thus market survival and success. In order to examine the perception of new entrepreneurs about the basic determinants of sustainable competitiveness, a combined qualitative and quantitative research methodology was used. The research is based on the assumption that new entrepreneurs in Bosnia and Herzegovina during the critical first three years of business focus on quantitative factors and indicators of market success, while neglecting consumer satisfaction and loyalty as fundamental determinants of the marketing concept. Quantitative research was conducted using a questionnaire that surveyed 156 owners and/or managers of new business ventures in Bosnia and Herzegovina. 12 in-depth interviews with the owners of new entrepreneurial ventures were also conducted to ensure a deeper understanding of the meaning of the data collected by the questionnaire. The presented research results can help when providing appropriate advisory and educational services to novice entrepreneurs in the territory of Bosnia and Herzegovina.